2021
DOI: 10.1155/2021/8897906
|View full text |Cite
|
Sign up to set email alerts
|

The Role, Function, and Mechanism of Long Intergenic Noncoding RNA1184 (linc01184) in Colorectal Cancer

Abstract: Background. Long intergenic noncoding RNA1184 (linc01184) has been recently discovered; however, its role in human diseases is limited to date. The present study is aimed at investigating the expression pattern and mechanism of linc01184 in colorectal cancer (CRC) tumorigenesis. Methods. The expression of linc01184 in CRC tissues and cell lines was compared with that in normal controls. The functions of linc01184 in CRC cells were identified by overexpression and small interfering RNA (siRNA) approaches in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Silencing LINC01006 suppresses the viability of HCC cells in vitro and suppresses tumor growth in vivo [33]. The roles of LINC00847 and LINC01184 have not been reported in HCC, but several studies have demonstrated that they have a carcinogenic effect in many other cancers [34][35][36]. Thus, a novel mRNA-miRNA-lncRNA network has been established to be associated with the hepatocellular carcinoma prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing LINC01006 suppresses the viability of HCC cells in vitro and suppresses tumor growth in vivo [33]. The roles of LINC00847 and LINC01184 have not been reported in HCC, but several studies have demonstrated that they have a carcinogenic effect in many other cancers [34][35][36]. Thus, a novel mRNA-miRNA-lncRNA network has been established to be associated with the hepatocellular carcinoma prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sui et al demonstrated that LINC01184 was highly expressed in colorectal cancer, and it could affect the the proliferation and invasion of colorectal cancer cells through the linc01184-miR-331-HER2-p-Akt/ERK1/2 pathway 49 . Subsequently, the risk score was calculated and separated all patients into highand low-risk subgroups based on median risk score, and Kaplan-Meier survival curves indicated that the high-risk groups had poorer clinical results than that of the low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01614 is associated with clinical stage in patients with glioma and NSCLC [15,25]. LINC01184 is associated with the several clinicopathological profiles of rectal cancer, including clinical stage, tumor size, lymph nodes, and distal metastasis [26]. Regarding LINC00900, Wang et al showed that the expression of LINC00900 increased with tumor grade in patients with primary glioblastoma [27].…”
Section: Discussionmentioning
confidence: 99%